Carbon-Based Nanomaterials via Heterojunction Serving as Photocatalyst - Syed, Noureen; Huang, Jianfeng; Feng, Yongqiang; Wang, Xiao; Cao, Liyun (Frontiers in Chemistry, 2019)
Photocatalytic hydrogen production from water splitting is of auspicious possibility to resolve the energy shortage and environmental anxieties. In the past decade, the combination of different carbon-based allotropes with semiconductors of different structure and unique properties to construct heterojunction, which can improve the charge separation, light absorption and steadiness, offer a promising way to achieve efficient photocatalyst. This review aims to provide an overview of the development for the carbon nanomaterials (CNMs)-based photocatalysts used for hydrogen production from water splitting and photocatalytic degradation of organic pollutants in waste water. The recent progress of CNMs-based heterojunction, including various composite with graphene, fullerene, carbon quantum dots (CQDs) and carbon nanotubes (CNTs) were highlighted. Furthermore, a typical model of CNMs-based Z-scheme heterojunction was also addressed. Finally, a promising perspective on the future development of CNMs-based photocatalysts have been discussed.